TOLERANSI DAN PEMAHAMAN ANTAR BUDAYA: FPK SEBAGAI PILAR PERSATUAN DI KALIMANTAN BARAT - Noviandra, Rezha; Syamsuri, Syamsuri; Purnama, Shilmy (Universitas Tanjungpura, 2024)
This research aims to determine and describe the role of the West Kalimantan National Assimilation Forum in realizing community unity and unity in West Kalimantan. The research method used is a descriptive method in the form of qualitative research. The data collection techniques used were observation, interviews and documentation. Data analysis techniques use data reduction analysis, data presentation, and drawing conclusions. The results of this research show that the role of the National Assimilation Forum in realizing unity and unity can be seen from the work program implemented, namely the production of short videos regarding national assimilation, socialization of national assimilation, youth dialogue, coordination and hearings of district/city FPK. With supporting factors such as coaching and coordinating with regional heads through the Kesbangpol agency, funding from the regional government to carry out work program activities, participation of cross-ethnic organizations in carrying out activities, collaboration with other community organizations in carrying out activities and obstacles to activities such as lack of funds provided by the regional government to carry out all work programs and members who are not active in carrying out activities.